RASIONALITAS PENGGUNAAN ANTIPSIKOTIK PADA PASIEN SKIZOFRENIA DI PUSKESMAS-PUSKESMAS KABUPATEN INDRAGIRI HULU - Agustini, Tiara Tri; Salsabilla, Fadia Rahma; Mora, Enda (Ensiklopedia of Journal, 2024)
Rationality of drug use is the rational use of drugs in which patients receive treatment according to clinical needs. Indragiri Hulu Regency has a total of cases of People with Mental Disorders (PMD) until December 2020, there were 553 cases with the highest number being schizophrenia as many as 393 cases. Antipsychotics were the first drug therapy to be effective in treating schizophrenia. This study aims to determine the rationality of the use of antipsychotics with rationality indicators referring to the World Health Organization which includes the right indication, right patient, right drug, right dose, and alert for side effects. The sample in this study were schizophrenic patients in 10 health centers in Indragiri Hulu Regency with the highest number of patients. This research is descriptive analytic done retrospectively. The results of this study are the right indication 100%, the right patient 100%, the right drug 98,77%, the right dose 61,72%, and the alert for side effects 71,60%.  Keywords: rationality, schizophrenia, antipsychotic